Bionomics and distribution of malaria vectors in Kisumu city, Western Kenya: implications for urban malaria transmission - Maxwell G. Machani; Shirley A. Onyango; Irene Nzioki; Sylvia Milanoi; Godfrey Nattoh; John Githure; Harrysone Atieli; Chloe Wang; Ming-Chieh Lee; Goufa Zhou; Andrew K. Githeko; Yaw A. Afrane; et al. (Malaria Journal)
Abstract Background Increasing unplanned urbanization in tropical Africa may create new niches for malaria vectors, raising transmission risk, yet control efforts focus on rural ecosystems. Understanding mosquito diversity, ecology and biting behaviour in urban areas is crucial for effective control. This study assessed Anopheles diversity, abundance, behaviour, and Plasmodium infection rates in Kisumu city, Kenya. Methods Indoor and outdoor host-seeking and resting adult mosquitoes were collected using CDC miniature light traps (CDC-LT) and Prokopack aspirators along an urban–rural transect. Anophelines were identified morphologically, with Anopheles gambiae sensu lato (s.l.) and Anopheles funestus group further distinguished to siblings using polymerase chain reaction (PCR). Sporozoite infection rates were determined using a multiplexed real-time quantitative PCR (qPCR) assay. Results A total of 3,394 female Anopheles mosquitoes were collected: An. gambiae s.l. (68%), An. funestus s.l. (19.8%), Anopheles coustani (7.8%), Anopheles pharoensis (2.6%), Anopheles maculipalipis (1.6%), and Anopheles leesoni (0.2%). All six species were found in urban zone, but only three were in peri-urban and rural sites. Overall, urban collection accounted for 55.5% of mosquitoes, followed by peri-urban (30%) and rural sites (14.5%). Anopheles arabiensis dominated urban (84.3%) and peri-urban (89%) sites, while An. gambiae sensu stricto (s.s.) was predominant in rural zone (60.2%) alongside An. arabiensis (39.7%). Anopheles funestus was predominant in peri-urban (98.4%) and rural (85.7%) areas, while An. leesoni accounted for 1.6% and 14.3%, respectively. In urban areas, all An. funestus s.l. samples were An. funestus s.s. . Most (55.5%) of Anopheles mosquitoes were collected indoors, while secondary vectors were mainly outdoors. Overall, sporozoite rates were higher outdoors (3.5%) than indoors (1.45%) in rural areas. Indoor rates were 2.5% (An. funestus), 1.4% (An. gambiae s.s.), and 1% (An. arabiensis). Outdoors, An. gambiae had 5.3%, and An. arabiensis 2.1%. In peri-urban areas, An. gambiae had 2.3%. No sporozoites were found in urban samples. Conclusion The study highlights a shift in Anopheles diversity towards urban areas with increased outdoor activity and outdoor malaria transmission in rural and peri-urban areas, underscoring the need for tools targeting outdoor-biting mosquitoes. The presence of An. funestus in urban settings emphasizes the need for sustained entomological surveillance to inform integrated vector control.